The legal regime of collective labor agreements - جنيدي صفاء (Latakia University Journal - Economic and Legal Sciences Series, 2023)
A collective labor contract (CCT) is an agreement between employers’ or employers’ unions and trade unions aimed at regulating working conditions. The contracting party representing employers may consist of one or more employers or one or more employers’ associations. The legislator discussed it in Articles 177 to 202 of the Labor Code. This contract is concluded with the aim of improving the working conditions for workers of a particular sector and contains special provisions regarding the conclusion, content and termination of the individual labor contract such as wages for sickness, maternity and working hours requirements. Work as a party to the collective contract. The collective labor contract is a very important source of labor rights. CCTs are most of the time concluded with a period of validity, accompanied by a social peace clause taxable to both contracting parties.